Analisis Faktor Promosi Online Instagram yang Memengaruhi Keputusan Pembelian Kuliner - Doro Edi; Yenni Merlin Djajalaksana; Julianti Kasih (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
The existence of the Covid-19 pandemic in Indonesia since March 2020, especially with the entry of the Delta variant in mid-2021, creates extraordinary challenges for all business people. Culinary businesses have started implementing sales with the concept of e-commerce through marketplaces such as Shopee, Tokopedia, and BukaLapak, as well as selling directly via Whatsapp, Facebook, Instagram or other social communication media. This study examines the factors in online promotion through Digital Marketing techniques specifically through Instagram that influence online culinary purchasing decisions since the Covid-19 pandemic. Primary data collection performed through online questionnaires and received 106 responses, the results of which were analyzed by multiple linear regression analysis. The results showed that the variables were valid and reliable. Multiple linear regression analysis for 5 models with the dependent variable being the type of Instagram post content with an alpha of 0.005 shows that there are 4 significant models and 1 insignificant model in the simultaneous effects on the dependent variable studied. The significant models are for Single-Post, Carousel Post, Reels, and Video, with the best R square in the Video independent variable model. The model with the dependent variable story that is not significant.